ANALISIS ALIH KODE DAN CAMPUR KODE INDONESIA MANDARIN DALAM INTERAKSI PEMBELAJARAN SASTRA CINA DI UNIVERSITAS BRAWIJAYA - Aisyah Cahya Ramadhani; Ressi Maulidina Delijar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study examines code-switching and code-mixing in Indonesian–Mandarin bilingual classroom interactions at the university level. The research aims to identify the forms, functions, and factors influencing their use in classroom communication. A descriptive qualitative approach with a case study design was employed in this study. Data were collected through classroom observations, recordings, and interviews, then analyzed using the Miles and Huberman model supported by the SPEAKING framework proposed by Dell Hymes. The findings indicate that code-switching and code-mixing serve as pedagogical strategies that help facilitate students’ comprehension and encourage classroom participation. Their occurrence is influenced by several contextual factors, including classroom situation, participant roles, communicative purposes, and students’ language proficiency.